HUBUNGAN USIA DAN PARITAS IBU BERSALIN DENGAN KEHAMILAN SEROTINUS DI KLINIK BIDAN SURIANI KISARAN TAHUN 2020 - Eliza Bestari Sinaga (Jurnal Maternitas Kebidanan, 2020)
Serotinus labor is one of the causes of the infant mortality rate in Indonesia at the age of 0-6 years of 2.80%, serotinus delivery is quite risky because it can cause complications both for mothers and infants. Several studies have shown that serotine delivery can increase the risk of endometritis, postpartum hemorrhage, and thromboembolic disease in birth mothers. The study aims to determine whether there is a relationship between age and parity of maternity mothers with pregnancy serotinus in suriani clinics in 2020. This type of research is analytic with cross sectional design that aims to determine the relationship of age and parity with serotine pregnancy. The data source in this study is primary data measured using an instrument in the form of a questionnaire and analyzed with the Chi-square correlation technique using the SPSS program. The population in this study were mothers who gave birth, taking samples by total sampling as many as 30 people. The results showed that there was a relationship between age and parity of maternity mothers with the incidence of serotine pregnancy. It is recommended that maternal mothers always check their pregnancy to doctors and midwives in order to prevent the occurrence of serotine pregnancy. Keywords: Age, Parity, Serotinus Pregnancy